PEMBAHARUAN HUKUM KELUARGA ISLAM DI INDONESIA (STUDI PEMIKIRAN PROF. DR. SITI MUSDAH MULIA TENTANG POLIGAMI) - Wardana, Afdhal (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
In the context of the problem of polygamy, Siti Musdah Mulia formulates polygamy as a marriage bond in which the husband marries more than one wife at the same time. Men who do this form of marriage are said to be polygamous. This type of research is library research. Siti Musdah Mulia, polygamy is essentially a legal affair, and therefore hurts the wife's feelings even more. Based on this information, the author agrees with Mulia's opinion that regards polygamy as an affair. According to researchers that the reality of a polygamous husband begins with romance and to attract other women, the husband usually corners and bad-mouthed his wife in the hope of getting sympathy from the mistress. It seems impossible for a woman to fall in love with a married man if he flatters his wife. It is very rare for a husband to get love from another woman praising the harmony of his household let alone praise his wife. The legal reasons for the opinion of Siti Musdah Mulia that forbid polygamy today are the an-Nisa verse 3, and the an-Nisa verse 129 which means: And if you are afraid you will not be able to do justice to the (orphaned) rights of women (if you marry her), then marry (other) women whom you like: two, three or four. Then if you are afraid that you will not be able to do justice, then (marry) only one or slaves that you have. That is closer to not persecuting "(Surah an-Nisa: 3). And an-Nisa verse 129) which means: And you will never be able to do justice among your wives, even though You really want to do that, so don't be too inclined (to the one you love) until you let the others hang. And if you make improvements and keep yourself from cheating, then surely Allah is Forgiving, Most Merciful ". (4: 129).